PELATIHAN KOMPUTER DAN OPERASIONAL PEMELIHARAAN CLUSTER KOTAKU KABUPATEN PRINGSEWU (Jurnal PkM Pemberdayaan Masyarakat, 2022)
The revolution in the field of information technology and telecommunications has had both positive and negative impacts on all aspects of human life. The development of information technology can positively be used by the community to exchange information, develop businesses, improve economic standards, and others. The development of technology that continues to increase requires the community to be able to operate it, thus the community will be able to innovate by utilizing technological developments to improve economic levels. The training activities were carried out using two methods, namely the lecture method with material exposure and the practical method using the STMIK Pringsewu Computer Lab. By holding this computer training the community operates in running computers as a tool to achieve a better result and with maintenance training (clusters), the community is expected to have a high awareness to better care for and maintain personal computers or public computers. For two days in a row, we introduced and provided training to the community so that people would be aware of the importance of using computers and be able to take good care of them.